Low grade mosaicism in hereditary haemorrhagic telangiectasia identified by bidirectional whole genome sequencing reads through the 100,000 Genomes Project clinical diagnostic pipeline - Clarke,J; Alikian,M; Xiao,S; Kasperaviciute,D; Thomas,E; Turbin,I; Rose,G; Olupona,K; Cifra,E; Curetean,E; Ferguson,T; Redhead,J; et al. (Journal of Medical Genetics, 2020)
For rare inherited diseases an important question is what type of clinical diagnostic test to select, for instance Sanger-based single genesequencing; a high read depth gene panel; whole exomesequencingor whole genome sequencing. There is emerging recognitionthat a transmissible parental variant present at less than expected heterozygous frequency (due to mosaicism) may escape detection by certain methods. This risk has been proposed as a factor infavourof higher depth sequencingstrategies. Here we report a case where barely 30-fold depth whole genome sequencing through the 100,000 Genomes Project identified low grade mosaicismthat had been missed by conventional Sanger sequencing.